ANALISIS KELAYAKAN PENDIRIAN INDUSTRI ABON IKAN LELE DUMBO (Clarias gariepinus) DI KABUPATEN BOYOLALI, JAWA TENGAH - Muhammad Alvian Syahru Ramadoni; Astrella Angie Pramesti; Yanti Silvia Napitu; Khansa Tsabitah; David Edison Manalu; Teny Sylvia; Wilda Harlia Devita (PPPM POLTESA, 2026)
The high production of catfish (Clarias gariepinus) in Boyolali Regency, reaching a value of IDR 648.9 billion in 2023, opens strategic opportunities for value-added agro-industry development, such as catfish floss processing. The objective of this study was to analyze the feasibility of establishing a catfish floss industry at PT. ABELINDO in terms of market, technical, operational, legal, environmental, and financial aspects. This feasibility study was designed for a factory in Sawit District, Boyolali Regency, with a planned raw material capacity of 5,000 kg/day. Technical feasibility was analyzed through mass balance calculations and layout design using the Systematic Layout Planning (SLP) method. Financial feasibility was evaluated using Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PBP) indicators under an 8-year project life scenario with a 10% Minimum Attractive Rate of Return (MARR), along with a sensitivity analysis. Technical evaluation results indicate that the factory line is capable of producing a final yield of 1,100 kg of ready-to-pack floss per day, implementing an eco-friendly wastewater treatment plant (bio-filter system). Financially, the project with an initial investment of IDR 66,077,070,702 is declared highly feasible. The results recorded a positive NPV of IDR 48,022,235,309, an IRR of 27.44%, a BCR of 1.73, and a PBP achieved within 3 years and 1 month. Sensitivity analysis concluded that the project's risk tolerance remains feasible as long as operational production cost increases do not exceed 10% and selling price decreases do not surpass 10%.